Iceland : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Iceland's 2005 Article IV Consultation reports that new projects have rekindled rapid growth and the economy is exhibiting signs of overheating, with imbalances evident in inflation, the current account, and external debt. GDP grew at an average rate of 3.8 percent between 1995 and 2004, second only to Ireland among industrial countries. Major investment projects have contributed both to the high growth rate and to overall macroeconomic volatility because of their size relative to that of the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Price Level